Determining the FecXE Allele in Batur Ewes (Ovis aries) of Indonesia - Pintaka Bayu Putra, Widya; Margawati, Endang Tri; Samsudewa, Daud (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
Batur sheep (Ovis aries) is one of the Indonesian native sheep that originated from Banjarnegara Regency. This study aimed to detect the FecXE allele of Bone Morphogenetic Protein 15 (BMP15) in Batur ewes using the sequencing method. A total of six (6) Batur ewes were randomly selected for investigation. The results showed that three (3) ewes were detected as carrier animals (FecX+/ FecXE), and the other ewes were wild-type animals (FecX+/FecX+). Unfortunately, this study did not observe a mutant animal (FecXE/FecXE). It can be concluded that the presence of the FecXE allele in Batur ewes may affect the prolificacy trait since previous studies reported that heterzygous ewes have the largest litter size traits than in wild-type ewes. Keywords: Batur sheep, BMP15 gene, litter size, sequencing,